PENGEMBANGAN GAME EDUKASI UNTUK MENGATASI PERUNDUNGAN DI SEKOLAH MENENGAH PERTAMA - Pratiwi, Rimata Deby; Ayu Wulandari, Bunga; Habibi, Akhmad (Jurnal Muara Pendidikan, 2025)
Bullying in schools, especially at the junior high school (SMP) level, is a serious issue that can damage students' mental and social health, as well as create an unsafe learning environment. Therefore, it is important to develop effective strategies, such as educational Games, to educate students about the impact of bullying and create a safe learning environment. This study aims to describe the planning, design, development, and feasibility of an educational Game for SMP students. The method used is Research and Development, with subjects being grade IX students of SMP Negeri 7 Muaro Jambi. The Game development follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with validation from content and media experts and field trials. The research results show that the educational Game has high feasibility: 98% content expert validation, 90% media expert validation, 99% teacher response, and 87% field trial results. The Game also received an 85% score for attractiveness, indicating that it is appealing to students. Based on these results, the educational Game is proven to be suitable as a solution to address bullying in SMP, while also serving as an effective and engaging media tool for students.